THE IMPORTANCE OF LITERATURE, CINEMA, THEATER, FINE ARTS IN EDUCATING STUDENTS IN THE SPIRIT OF MILITARY PATRIOTISM - Agzamov Inom Salimjonovich; Orazaliyev Nuriddin Bekmurat o‘g‘li (Journals Park Publishing, 2023)
When we talk about military-patriotic education, we mean the full and creative use of all forms and methods at our disposal, which are clearly aimed at influencing people's emotions and minds.